2010
DOI: 10.2174/138920210790217981
|View full text |Cite
|
Sign up to set email alerts
|

Expressional Analysis and Role of Calcium Regulated Kinases in Abiotic Stress Signaling

Abstract: Perception of stimuli and activation of a signaling cascade is an intrinsic characteristic feature of all living organisms. Till date, several signaling pathways have been elucidated that are involved in multiple facets of growth and development of an organism. Exposure to unfavorable stimuli or stress condition activates different signaling cascades in both plants and animal. Being sessile, plants cannot move away from an unfavorable condition, and hence activate the molecular machinery to cope up or adjust a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(52 citation statements)
references
References 104 publications
0
50
0
Order By: Relevance
“…Although RLKs have been found to be important regulators of root hair growth in Arabidopsis under low-P conditions (Lan et al, 2013), their role seems to be much more general, as they also function in defense and stress responses, including drought, salinity, and cold (Lehti-Shiu et al, 2009;Ye et al, 2009;Das and Pandey, 2010;Marshall et al, 2012;Schulz et al, 2013;Vivek et al, 2013), possibly acting as hubs in stress signaling and development (Das and Pandey, 2010;Asano et al, 2012;Schulz et al, 2013). Several RLKs such as CRPK1 have been shown to play key roles in abiotic stress tolerance, positively or negatively regulating stress tolerance by modulating abscisic acid signaling and reducing the accumulation of reactive oxygen species (Lan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although RLKs have been found to be important regulators of root hair growth in Arabidopsis under low-P conditions (Lan et al, 2013), their role seems to be much more general, as they also function in defense and stress responses, including drought, salinity, and cold (Lehti-Shiu et al, 2009;Ye et al, 2009;Das and Pandey, 2010;Marshall et al, 2012;Schulz et al, 2013;Vivek et al, 2013), possibly acting as hubs in stress signaling and development (Das and Pandey, 2010;Asano et al, 2012;Schulz et al, 2013). Several RLKs such as CRPK1 have been shown to play key roles in abiotic stress tolerance, positively or negatively regulating stress tolerance by modulating abscisic acid signaling and reducing the accumulation of reactive oxygen species (Lan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that both CRK3 and CRK2 play a role in the phosphorylation of these TFs in plants. On the other hand, previous studies have also suggested that some CRKs are involved in the signal transduction of different extracellular stimuli such as salt, low/high-temperature stress, wounding, and phytohormones in Arabidopsis, tobacco, tomato, and pea (61,(63)(64)(65)(66)(67). Phenome analysis based on genetic techniques might provide significant information regarding the role of CRK-dependent Tyr phosphorylation in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, srlk mutants failed to limit root growth in response to salt stress (de Lorenzo et al, 2009). A signal transduction pathway mediated by SRLK was linked to the activation of a member of the calcium-dependent protein kinase (CDPK) gene family (de Lorenzo et al, 2009), which is often linked to adaptation responses to biotic and abiotic stresses (Das and Pandey, 2010).…”
Section: A New Approach: Rlks and Drought Stressmentioning
confidence: 99%